2016
DOI: 10.1002/cphc.201600326
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Spectroscopic Markers of Hydrogen Bonds

Abstract: Quantum calculations are used to examine whether an AH⋅⋅⋅D H-bond is unambiguously verified by a downfield shift of the bridging proton's NMR signal or a red (or blue) shift of the AH stretching frequency in the IR spectrum. It is found that such IR band shifts will occur even if the two groups experience weak or no attractive force, or if they are drawn in so close together that their interaction is heavily repulsive. The mere presence of a proton-acceptor molecule can affect the chemical shielding of a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 98 publications
(133 reference statements)
0
12
0
Order By: Relevance
“…The method is based [49] on the notion that when placed between two atoms that are potentially H-bonded to one another, the chemical shielding of the bridging proton derives from two separate phenomena. In the first place, there is what might be called a positional effect σ p .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method is based [49] on the notion that when placed between two atoms that are potentially H-bonded to one another, the chemical shielding of the bridging proton derives from two separate phenomena. In the first place, there is what might be called a positional effect σ p .…”
Section: Methodsmentioning
confidence: 99%
“…An attempt was made in this direction recently [49] in a study which considered the effects of HBs on IR and NMR spectral data. It was shown that the red shift of the A-H··B HB is not necessarily indicative of an attractive interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept, therefore, of a three center – four electron sharing due to resonance type n B → interaction: O–H: O ↔ O: H–O may be the basis for a revised IUPAC definition of the hydrogen bond [ 89 ]. This linear correlation between Wiberg bond order and δ( 1 H) may resolve the ambiguity that a deshielded bridging proton signal is a necessary but not sufficient demonstration of a hydrogen bond [ 90 ]. As pointed out by Scheiner [ 90 , 91 ], deshielding effects can be observed in cases of the proximity of an electron cloud of a second molecule even if no hydrogen bond is present.…”
Section: Hydrogen Atomic Positions Of Intramolecular O–h···o Hydromentioning
confidence: 99%
“…This linear correlation between Wiberg bond order and δ( 1 H) may resolve the ambiguity that a deshielded bridging proton signal is a necessary but not sufficient demonstration of a hydrogen bond [ 90 ]. As pointed out by Scheiner [ 90 , 91 ], deshielding effects can be observed in cases of the proximity of an electron cloud of a second molecule even if no hydrogen bond is present.…”
Section: Hydrogen Atomic Positions Of Intramolecular O–h···o Hydromentioning
confidence: 99%